PENGUNAAN MODEL PEMBELAJARAN INQUIRI SOSIAL UNTUK MENINGKATKAN BERFIKIR KRITIS PESERTA DIDIK KELAS XI IPS 1 PADA MATA PELAJARAN SEJARAH DI SMA NEGERI 2 MENGGALA - Ima Suri (KOLONI, 2022)
The purpose of this study was to determine the implementation of learning history subjects using the Social Inquiry Learning Model and measure the effectiveness and improvement of students' critical thinking skills. The method used in this research is a class action method. The object of this research is the Social Inquiry Learning Model to improve students' critical thinking skills and self-concept. Data collection tools used are tests and observations. The results of this study indicate 1) the Social Inquiry Learning Model can be used in the learning process in history subjects 2.) There is a significant increase in students' critical thinking skills by using the Social Inquiry Learning Model based on the results of tests carried out at the end of each cycle I and II with the increase in students' critical thinking skills between cycles reached 29% with the success rate of students who were able to achieve indicators of critical thinking were 27 students or 87% of the 31 students who were subjected to the action. Keywords: Learning Models, Social Inquiry, Critical Thinking, History Lessons